The Effect of Transformational Leadership on Employee Performance During The Covid-19 Pandemic with Control Culture and Affective Commitments as Intervening Variables - Pratiwi , Heni Indah; Hanifah, Imam Abu; Ibrani, Ewing Yuvisa (Journal of Applied Business, Taxation and Economics Research, 2024)
Study this aim for test Influence Leadership Transformational to Performance Employee with Culture Control and    Affective Commitment as an intervening variable. This research is one of a kind quantitative research, data were collected using primary data and questionnaires to obtain information from respondents, namely middle managers who work in company manufacture in Province Banten. Method analysis which used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) Path Modeling with SmartPLS 3.0 analysis tool. The results of this study are 1) Transformational Leadership affects the Culture of Control, Commitment Affective and Performance Employee 2) Culture Control and Commitment Affective take effect to Performance Employee. 3) Leadership Transformational effect on Employee Performance through the Culture of Control and Commitment Affective.